Youth and Entrepreneurial Intentions in four South-East European Countries - Rajh, Edo; Jovanov Apasieva, Tamara; Budak, Jelena; Ateljević, Jovo; Davčev, Ljupčo; Ognjenović, Kosovka (Senate Hall, 2018)
We combine variables from the Theory of Planned Behaviour with additional personality trait and contextual variables to explain entrepreneurial intentions of 1,200 students of economics and business in four South-East European countries: Bosnia and Herzegovina, Croatia, Macedonia and Serbia. Among these four countries, entrepreneurial intentions are highest in Macedonia. This can be explained by perceptions such as personal attitude towards entrepreneurship and perceived behavioural control, which positively affect entrepreneurial intentions and which are found to be higher on average in Macedonia. Another striking finding is the lack of explanatory power of the contextual variables (in particular perceived barriers for entrepreneurship) in these countries which are known for their poor business climate. The present study indicates that although young people in these four transition countries hold a positive attitude towards entrepreneurship, they don't show a clear entrepreneurial intent. Keywords: entrepreneurship, entrepreneurial intentions, transition countries, South-East Europe, Theory of Planned Behaviour
Keywords: entrepreneurship|entrepreneurial intentions|transition countries|South-East Europe|Theory of Planned Behaviour